A guiding framework for the development of a trans-disciplinary community mental health student teaching and learning platform - Jansen, J.M.; du Preez, M.; Exner, R.; Stroud, L. (South African Journal of Higher Education, 2017)
Establishing a trans-disciplinary mental health platform could contribute to outreach and service training agendas in a higher educational context. The purpose of the platform described in the article provides an opportunity for students to learn from each other, with each other and about each other, across a variety of disciplines in one university, while also effectively addressing the needs of the surrounding community. This article records the background to the establishment of a unique multi-disciplinary university-community collaborative initiative in South Africa by using a self-reflective, action research approach. It also identifies lessons learnt and creates a guiding framework for the establishment of similar projects in other communities. It contributes firstly, to provide a framework to guide and encourage future establishments of similar university-community collaborative engagement endeavors and, secondly, to highlight the requirements for sustaining services to communities when senior students exit their university programmes, while new students enter.